A randomised controlled trial comparing compression therapy after radiofrequency ablation for primary great saphenous vein incompetence. (March 2016) - Krasznai, AG; Sigterman, TA; Troquay, SAM; Houtermans-Auckel, JP; Snoeijs, MGJ; Rensma, HG; Sikkink, CJJM; Bouwman, LH
Background: Optimal duration of leg compression after venous ablation remains unclear. This randomised controlled trial evaluates 4 h compared to 72 h of leg compression. Methods: Patients were randomised to 4 or 72 h of leg compression after radiofrequency ablation of the great saphenous vein. Primary outcome was change in leg volume after 14 days. Secondary outcomes were postoperative pain, complications and time to full recovery. Results: Patients wearing compression stockings for 4 h after treatment had a 64 mL (95%CI: − 23 to + 193) reduction in leg volume, compared to an increase of 21 mL (95%CI: 8.33–34.5) in patients wearing compression stockings for 72 h ( P  = 0.12). Patients wearing compression stockings for 4 h experienced fewer complications (16% vs. 33%, P  = 0.05). Postoperative pain and time to full recovery did not differ significantly. Conclusion: Wearing compression stockings for 4 h is non-inferior in preventing leg oedema as wearing compression stockings for 72 h.